Health Professionals Job Satisfaction and Associated Factors in Ethiopia: A Systematic Review and Meta-analysis. (November 2021) - Tenaw, Zelalem; Siyoum, Melese; Tsegaye, Berhan; Werba, Tehsale Biku; Bitew, Zebenay Workneh
Background: Health professionals' job satisfaction is crucial for health professionals' life which determines health care service quality. This study aimed to estimate pooled prevalence of job satisfaction of health professionals and associated factors in Ethiopia. Methods: Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) was followed to prepare this study. Studies were searched from PubMed (EBSCOhost), Directory of open access journals (DOAJ), Global health, African Index Medicus, IRIS (WHO digital publication), African Journals Online (AJOL), Google Scholar, and Google. Random-effect model was used to estimate the pooled prevalence of job satisfaction and associated factors. Heterogeneity was assessed using I 2 test statistics. Publication bias was checked using funnel plot, Egger's regression test, and sensitivity analysis. Result: The pooled prevalence of health professionals' job satisfaction was computed from 35 studies, and it was 46.68% (95%, confidence interval (CI): 41.82, 51.54, I 2 = 95.8%). Specifically, job satisfaction was 57.56%, 48.80%, 48.57%, 48.48%, 44.56%, 39.20%, and 16.5% among pharmacy professionals, health officers, midwives, nurses, anesthetists, physicians, and health extension workers, respectively. Secured working environment (pooled odds ratio [POR] = 6.50, 95% CI: 3.41-9.58), coworkers relationship (POR = 5.14, 95% CI: 1.27, 9.02), good relationship with supervisors (POR = 5.86, 95% CI: 2.56-9.16) and having bachelor's degree (POR = 2.52, 95% CI: 1.31, 3.72) were significantly associated with job satisfaction. Conclusion: Job satisfaction among Ethiopian health professionals is considerably low. Secured working environment, positive relationships among staff, and having a bachelor's enhanced the job satisfaction. Designing strategies to improve safety in the work environment and improved communication among workers could improve job satisfaction.